Upper Gastrointestinal Tract Foreign Bodies - Young Eun Oh; Hee Seok Moon (Yong Chan Lee, 2024)
Foreign body ingestion, a common emergency encountered in clinical practice, is a potentially serious condition. Most foreign bodies in the gastrointestinal tract pass spontaneously. However, objects that are relatively long or large may lodge in the upper gastrointestinal tract, potentially causing perforation, bleeding, and obstruction. This literature review summarizes the natural history and clinical aspects of these types of foreign bodies in adults as well as the various methods for their removal. Endoscopic removal is a relatively safe and effective procedure for removing these types of foreign bodies. The development of endoscopic techniques and devices has resulted in their widespread use, with good results, as the primary treatment.